Self-efficacy for Critical Care Nurses in Al-Muthanna Governorate - Fouad Salam Naeem, Aqeel Habeeb Jasim, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To assess the level of self-efficacy of critical care nurses at Al- Muthanna governorate hospitals. Methods: The Self-efficacy of Critical Care Nurses in Al-Muthanna governorate were measured using a descriptive analytic design. A non-probability, purposeful sample of 95 nurses who work in hospital ICU and CCU units (Al-Hussein Teaching Hospital and Al-Khader General Hospital and Rumaitha General Hospital and Al-Shahid Youssef Najm Hospital). The data for this study were analyzed with SPSS 26 (version) to get the results. Results: self-efficacy among nurses; the mean scores indicate moderate to high self-efficacy in which the items 2, 3, 5, 6, and 8 show moderate level while items 1, 4, 5, 7, 9, and 10 show high level. 55.2% of nurses are showing moderate level of self-efficacy while 43.7% of them are showing high self-efficacy. Conclusions: The findings showed that more than one half of nurses are moderate level of self-efficacy.